Protection of the Future Harbor Area AC Microgrids Containing Renewable Energy Sources and Batteries - Memon, Aushiq Ali; Kauhaniemi, Kimmo (IEEE, 2023)
A significant share of global carbon emissions is related to marine vessels running solely on fossil fuels. The hybrid or fully electrified marine vessels using battery energy storage systems (BESS) both for onboard propulsion system and for cold-ironing during docking at harbor areas will significantly reduce marine related carbon emissions. However, the transformation of marine vessels’ operations from diesel engines to BESS will necessarily require charging stations and other electric power infrastructure at harbor areas. The sustainable and cheap energy of renewable energy sources like wind turbine generators (WTGs), photovoltaic (PV) systems and related BESS could be used at harbor areas for charging depleted vessel-BESS and supplying power to cold-ironing loads. For this purpose, two new harbor area smart grid or AC microgrid models have been developed by our research group. This paper presents a comprehensive analysis of three-phase short-circuit faults for one of the proposed AC microgrid models using PSCAD/EMTDC simulations. The fault study of harbor area AC microgrid-1 is done for both grid-connected and islanded modes. The main purpose of the fault study is to check if grid-connected mode overcurrent settings of intelligent electronic devices (IEDs) will also be valid for different islanded mode fault cases with different fault current contributions from converter-based distributed energy resources (DERs) including WTG, PV and BESS. The extent of fault current contribution from DERs and BESS to avoid adaptive protection settings and to ensure definite-time protection coordination and fast fuse operations during different islanded modes is investigated.
Keywords: Adaptive overcurrent protection; batteries; converter-based DERs; fuse; harbor area ac microgrids; islanded mode; short-circuit faults; renewable energy sources; fi=Sähkötekniikka|en=Electrical Engineering|